Impact of heat stress on buffalo production trend and reproductive efficiency in tropical climate and mitigation strategies: A review - Tampubolon, Yusni Khairani; Saragih, Winda Fransisca (Journal of Advanced Veterinary Research, 2026)
Increasing environmental temperatures is one of the extreme conditions resulting from climate change. Temperatures exceeding the thermoneutral zone in livestock can trigger heat stress. This review provides information regarding the effects of heat stress on the productivity and reproduction of buffalo. In tropical countries such as Indonesia, the buffalo species include swamp buffalo (Bubalus bubalis) and river buffalo (Murrah buffalo). Buffalo can tolerate environmental temperatures up to 27.6°C, with an ideal environmental temperature range of 16-24°C. The tropical climate data showed that over the past decade, the temperature increased by approximately 0.8°C annually. If this condition continues it will disrupt the thermoregulatory mechanisms of buffalo, triggering hormonal changes, decreasing milk and meat production, and decreasing reproductive efficiency. Mitigation strategies through cooling methods, the use of sensor-based technology and artificial intelligence, also feed supplementation have shown positive results. Genetic selection and assisted reproductive technology (ART) techniques are promising approaches for increasing the resilience and productivity of buffalo to heat stress. A comprehensive and solution-based scientific approach is essential to achieving sustainable buffalo farming despite the challenges of global climate change.